Prognostic methylation markers for overall survival in cytogenetically normal patients with acute myeloid leukemia treated on SWOG trials. Issue 13 (21st February 2017) - Qu, Xiaoyu; Othus, Megan; Davison, Jerry; Wu, Yu; Yan, Liying; Meshinchi, Soheil; Ostronoff, Fabiana; Estey, Elihu H.; Radich, Jerry P.; Erba, Harry P.; Appelbaum, Frederick R.; Fang, Min
Abstract : BACKGROUND: Aberrant DNA methylation is known to occur in patients with acute myeloid leukemia (AML), whereas methylation signatures and prognostic markers have been proposed. The objective of the current study was to evaluate all CpG sites of the genome and identify prognostic methylation markers for overall survival in patients with AML with normal karyotype (AML‐NK). METHODS: AML‐NK samples from 7 SWOG trials were analyzed using a novel genome‐wide approach called "CHARMcox" (comprehensive high‐throughput array‐based relative methylation analysis combined with the Cox proportional hazards model) controlling for known clinical covariates. CHARMcox was applied to a phase 1 discovery cohort (72 patients) to identify survival‐associated methylation regions (SAMRs). Subsequently, using bisulfite pyrosequencing, SAMRs were studied in phase 2 model‐building (65 patients) and phase 3 validation (65 patients) cohorts. An independent external cohort from The Cancer Genome Atlas (TCGA) AML study (LAML) was used for further validation (93 patients). RESULTS: Two SAMRs, located at the CpG island shores of leucine zipper tumor suppressor 2 ( LZTS2 ) and nuclear receptor subfamily 6 group a member 1 ( NR6A1 ), respectively, were identified. Multivariable analyses demonstrated that hypomethylation of either LZTS2 or NR6A1 was associated with worse overall survival in the SWOG cohort ( P <.001). The prognosis was validated in patients with AML‐NK from the TCGA‐LAML cohort. Methylation values below the median at both markers predicted worse overall survival (SWOG: hazard ratio, 1.89 [ P <.001]; and TCGA‐LAML: hazard ratio, 2.08 [ P= .006]). The C‐statistic was 0.71 for both cohorts, and the impact was independent of the Fms‐related tyrosine kinase 3 internal tandem duplication ( FLT3 ‐ITD) status. CONCLUSIONS: The 2 methylation markers, measurable by clinically applicable assays such as bisulfite pyrosequencing, are promising for risk stratification among patients with AML‐NK. Cancer 2017;123:2472–81. © 2017 American Cancer Society . Abstract : Hypomethylation of either leucine zipper tumor suppressor 2 ( LZTS2 ) or nuclear receptor subfamily 6 group a member 1 ( NR6A1 ) is associated with worse overall survival in patients with acute myeloid leukemia with normal cytogenetics. The prognostic impact appears to be independent of age, performance status, white blood cell and platelet counts, and Fms‐related tyrosine kinase 3 internal tandem duplication ( FLT3 ‐ITD) status.